The production of housing policies through performativity. Understanding the emergence of new state interventions in Berlin. - Weber-Newth, Francesca; Helbrecht, Ilse (Springer VS, 2019)
In dem Text geht es um das Berliner Modell der Kooperativen Baulandentwicklung. Anhand von Experteninterviews mit Akteuren, die an der Implementierung des Modells in Berlin beteiligt sind, wird mit Hilfe der Performativitätstheorie das Handeln von Politikern, Anwälten, Planern und Verwaltungsmitarbeitern diskutiert.

Housing is one of the most regulated policy areas in Germany and a highly controversial political field in Berlin. Against a backdrop of significant growth- whether population figures, tourism, or rising rents-we scrutinize recent efforts of municipal authorities in Berlin to tackle the 'new housing question'. On a theoretical level we argue that the housing market is made, and the interesting questions centre on this process of making as the object of study. Performativity theory (Butler 1997) provides a way of seeing the housing market, a language to describe the interaction between planning rules and their lived expression as practised and produced via the roles of different actors. Our case study is the development and implementation of a regulatory planning instrument 'Kooperative Baulandentwicklung' introduced in Berlin in 2014. Commonly known as 'developer contributions' the instrument requires developers to pay for the physical and social infrastructure needed for a new development, in addition prescribing 30 % social housing. Drawing on expert interviews with actors involved in implementing the planning tool in Berlin, we use performativity theory to discuss the "role-playing" of politicians, lawyers, planners and administration employees, who produce the instrument through everyday performances. While developer contributions only work within a cycle of economic growth and cannot provide a cardinal solution to the Housing Question, dynamic and subtle role-playing has meant that the Berlin housing market is a more regulated space since 2014. Our paper is not only a local story, but also one of wider political relevance-indicating what it takes to tighten the regulatory screws.
Keywords: Wohnungspolitik; Großstadt; Metropole; Baulandpolitik; Baulandentwicklung; Kooperation; Public-Private-Partnership; Kommunale Wohnungspolitik; Wirkungsanalyse; Performativität; Kooperative Baulandentwicklung